Elucidation and application of the neuroimmune axis between depression and autoimmune diseases: A genome wide and cohort study - Fu Sun; Shirong Hui; Bin Gong; Jinhua Gu; Peng Huang (PLoS ONE, 2025)
The neuroimmune axis, a critical communication network between the nervous and immune systems, has been implicated in the comorbidity of depression (DeP) and autoimmune diseases (ADs). The shared genetic basis underlying these conditions, and its application are the focus of our investigation, using genome-wide association studies (GWAS) summary statistics and cohort data. We performed a comprehensive analysis, integrating genome-wide and local genetic correlations, casual gene and pleiotropic loci identification, and functional annotation. To improve the power of the identification of shared genes and loci, we proposed the local strategy that the sequential analysis was only in the significantly correlated regions. We defined significant genetic overlap between DeP and ADs, particularly idiopathic pulmonary fibrosis (IPF), rheumatoid arthritis (RA), and ulcerative colitis (UC), with shared loci and genes, such as rs7171171 and PLCL1 . With the casual relationship, we further defined the higher prediction performance of polygenic risk scores (PRS) for asthma when incorporating DeP. Besides the main analyses, we conducted various sensitivity analyses and side analyses to ensure the robustness of our results. This study not only advances our understanding of the genetic interplay between neuropsychiatric and autoimmune disorders but also provides a framework for future research aimed at targeted therapeutic interventions.